Does Off-Pump Coronary Artery Bypass Grafting Negatively Impact Long-Term Survival and Freedom from Reintervention?. (11th September 2013) - Raja, Shahzad G.; Husain, Mubassher; Popescu, Florentina L.; Chudasama, Dimple; Daley, Siobhan; Amrani, Mohamed
Abstract : Recently published evidence has raised concerns about worse late mortality and increasing need for reintervention after off-pump coronary artery bypass grafting. We undertook this study to assess the impact of off-pump coronary artery bypass grafting on survival and freedom from reintervention at 10 years. From January 2002 to December 2002, 307 consecutive patients who had isolated multivessel off-pump coronary artery bypass grafting at our institution were compared to a control group of 397 patients that underwent multivessel on-pump coronary artery bypass grafting during the same period. In addition, univariate and risk-adjusted comparisons between the two groups were performed at 10 years. Kaplan-Meier survival was similar for the two cohorts. After adjusting for clinical covariates, off-pump coronary artery bypass grafting did not emerge as a significant independent predictor of long-term mortality (Hazard Ratio 0.91; 95% Confidence Interval 0.70–1.12), readmission to hospital for cardiac cause (Hazard Ratio 0.96; 95% Confidence Interval 0.78–1.10), or the need for reintervention (Hazard Ratio 0.93; 95% Confidence Interval 0.87–1.05). Off-pump coronary artery bypass grafting compared with on-pump coronary artery bypass grafting does not adversely impact survival or freedom from reintervention at a 10-year follow-up.